2010
DOI: 10.1371/journal.pone.0015192
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glutamate Release on Voltage-Dependent Anion Channels (VDAC)-Mediated Apoptosis in an Eleven Vessel Occlusion Model in Rats

Abstract: Voltage-dependent anion channel (VDAC) is the main protein in mitochondria-mediated apoptosis, and the modulation of VDAC may be induced by the excessive release of extracellular glutamate. This study examined the role of glutamate release on VDAC-mediated apoptosis in an eleven vessel occlusion model in rats. Male Sprague-Dawley rats (250–350 g) were used for the 11 vessel occlusion ischemic model, which were induced for a 10-min transient occlusion. During the ischemic and initial reperfusion episode, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Wu et al (2009) reported the curves of adhesive force showed dramatic alterations in the viscoelasticity of red blood cells. Also, we previously reported that the changes in the adhesion force of mitochondria might be related to destruction of the highly dense mitochondrial outer membrane (Lee et al, 2011;Park et al, 2010). Halestrap et al (2007) showed that mitochondria in the fully open state led to the second sequence of MPTP opening and extensive swelling.…”
Section: Discussionmentioning
confidence: 96%
“…Wu et al (2009) reported the curves of adhesive force showed dramatic alterations in the viscoelasticity of red blood cells. Also, we previously reported that the changes in the adhesion force of mitochondria might be related to destruction of the highly dense mitochondrial outer membrane (Lee et al, 2011;Park et al, 2010). Halestrap et al (2007) showed that mitochondria in the fully open state led to the second sequence of MPTP opening and extensive swelling.…”
Section: Discussionmentioning
confidence: 96%
“…Although originally characterized as a mitochondrial porin, VDAC present at the plasma membrane appears to play different roles. Thus, this versatile porin has been related to extrinsic apoptotic pathways, cellular ATP release, calcium and metabolite transport, volume control, redox homeostasis and NADH:ferricyanide reductase activity (Akanda et al, 2008;De Pinto et al, 2010;Park et al, 2010). Moreover, in particular in neurons, some studies are starting to reveal the importance of VDAC in the events related to AD pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Voltage-dependent anion channel (VDAC) is the main protein in mitochondria-mediated apoptosis, and the modulation of VDAC can be induced by the excessive release of extracellular glutamate (Park et al, 2010;Zaid et al, 2005). Glutamate is the principal excitatory neurotransmitter in the brain and the excessive release of extracellular glutamate is a key factor that promotes neuronal cell death (Park et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate is the principal excitatory neurotransmitter in the brain and the excessive release of extracellular glutamate is a key factor that promotes neuronal cell death (Park et al, 2010). In brain, excess ammonia and glutamate is converted into glutamine via the enzyme glutamine synthetase (GS) for protecting neurons against excitotoxicity (Suárez et al, 2002).…”
Section: Discussionmentioning
confidence: 99%